1948
DOI: 10.1001/jama.1948.02900090005002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Problems in Penicillin Sensitivity

Abstract: accomplished by eliminating all chromium trim and by painting the top of the hood and dash a nonreflecting dull optical black. The use of such paint on metal aircraft has long been an established convention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

1950
1950
1970
1970

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(7 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…These authors described the gross morphology of these reactions and reported an incidence of 5 % in patients who had never received therapeutic penicillin. P eck et al (18) described a higher incidence of this reaction in patients who had recently had allergic reactions to penicillin, and discussed the possible clinical significance of a positive delayed skin test.…”
Section: Introductionmentioning
confidence: 99%
“…These authors described the gross morphology of these reactions and reported an incidence of 5 % in patients who had never received therapeutic penicillin. P eck et al (18) described a higher incidence of this reaction in patients who had recently had allergic reactions to penicillin, and discussed the possible clinical significance of a positive delayed skin test.…”
Section: Introductionmentioning
confidence: 99%
“…Chez les individus présentant une anamnèse ou des manifestations cliniques faisant suspecter une allergie à la pénicilline, l'injection intraderm ique de pénicilline n'évoque une réaction urticarienne que dans un pourcentage relativem ent faible de cas. C'est ainsi que l'on note un pourcentage de réactions positives allant de 0 % (sur 25 cas [16]) à 40% (sur 40 cas [17]). Dans la plus grande série de cas publiés (551 cas), le pourcentage de réactions urticariennes atteignait 23,5% [18].…”
Section: B) Test Par Injection Intradermiqueunclassified
“…Il semble cependant, d'après certains travaux, qu'une corrélation puisse exister entre une allergie à la pénicilline (quel qu'en soit le type) et une réaction de type tuberculinique. C'est ainsi que leur fréquence est plus élevée chez les patients présentant une anamnèse d'allergie à la pénicilline ou chez ceux ayant été traités avec de la pénicilline [16,30]. Sur une série de 33 patients présentant une réaction de ce type, près de 50 % réagirent par une m anifestation allergique à l'adm inistration ultérieure de pénicilline [32].…”
Section: ° Réaction Cutanées De Type Tuberculiniqueunclassified
“…Annals New York Academy of Sciences Such criteria are as follows: (6) The microbids must develop subsequent to the primary infection. (7) The microbids must usually be sterile. (8) A support for the conception of a skin eruption as an "id" lies in certain clinical characteristics: (a) appearance of the "ids" in showers; (b) tendency to symmetry in distribution because of hematogenous origin; (c) tendency to spontaneous involution after healing of the primary focus; (d) focal reactions after injection of sufficient amounts of microbidin.…”
Section: Pathogenesis Of Trichophylidsmentioning
confidence: 99%